Rapidly progressing metastatic malignant melanoma mimicking primary pleural tumor: A case report. Issue 9 (21st March 2022) - So, Clara; Yoshida, Tatsuya; Mizuno, Takaaki; Yatabe, Yasushi; Ohe, Yuichiro
Abstract: Malignant melanoma is the most aggressive skin cancer that originates from melanocytes. Primary or metastatic pleural melanoma shares clinical and imaging characteristics with primary pleural tumors, such as pleural mesothelioma. Identification of the primary site can be challenging to distinguish between primary and secondary melanomas. We report a case of a 46‐year‐old woman with metastatic, rapidly progressing pleural melanoma mimicking primary pleural tumor. The metastatic pleural tumor from a primary cutaneous melanoma was diagnosed by reevaluating a previous surgical specimen. When evaluating patients with pleural melanoma, the primary site should be reevaluated to distinguish between primary and secondary melanomas. Abstract : Primary or metastatic pleural melanoma shares clinical and imaging characteristics with primary pleural tumors, such as pleural mesothelioma. Identification of the primary site can be challenging to distinguish between primary and secondary melanomas. We report a case of a 46‐year‐old woman with metastatic, rapidly progressing pleural melanoma mimicking primary pleural tumor.